Water sorption properties of brewer's spent grain: A study aimed at its stabilization for further conversion into value-added products. (March 2023) - Sanches, Marcio Augusto Ribeiro; Augusto, Pedro Esteves Duarte; Polachini, Tiago Carregari; Telis-Romero, Javier
Abstract: Due to its high moisture content and perishability, the water adsorption isotherms, and thermodynamic properties of brewer's spent grain obtained from barley malt (BSGL) and wheat malt based (BSGW) were evaluated under storage and drying conditions. Chemically characterized BSGs were subjected to the static gravimetric method to experimentally obtain the water adsorption isotherms at ten temperatures (5–90 °C). As the best-fitted model (R 2 adj > 0.9928 e χ 2 ≤ 0.0001), the GAB parameters were used to determine the adsorption surface area, spreading pressure, and thermodynamic properties. At temperatures from 5 to 50 °C, the adsorption isotherms of BSGL and BSGW showed convex curves, typical of type III isotherms. However, at temperatures above 60 °C, the curves started to present typical type II isotherms with sigmoid-shaped sorption behavior. The equilibrium moisture content of BSGs increased with increasing relative humidity and/or decreasing temperature. The spreading pressure increased as the water activity and temperature increased, contrary to that observed for the adsorption surface area. Thermodynamic analysis showed that the net isosteric heat of adsorption, enthalpy, and differential entropy decreased as the equilibrium moisture increased. The compensation theory was confirmed, and its results indicated that the adsorption processes were enthalpy-driven. The positive values for Gibbs free energy indicated that the adsorption processes were not spontaneous, which may be related to the composition of BSGs in terms of lipids and proteins. From an energy and stability point of view, a water activity of 0.4 is the ideal condition for the storage of BSGs. Graphical abstract: Image 1 Highlights: Different brewery operations significantly affected the BSGs compositions. The GAB model best described the sorption isotherms in all conditions evaluated. Water binding properties were slightly hampered by the higher protein contents. The type of sorption isotherm of the BSGs was affected by temperature. Multi temperature sorption study provides useful thermodynamic functions.